LEARNING STYLES OF JAZZ CHORDS IN POP MUSIC PERFORMANCE (ON THE EXAMPLE OF GUITAR PLAYING). - B.Zokirov; Sa'dullayev Doniyorjon Sayfullayevich (Western European Studies, 2024)
This article explores the learning styles associated with incorporating jazz chords into pop music guitar performances. By examining various instructional methods, analyzing relevant literature, and assessing practical outcomes, the study aims to provide a comprehensive understanding of effective techniques for mastering this musical fusion. The results highlight the benefits of diverse learning approaches and offer recommendations for guitarists seeking to enhance their pop music performances with jazz influences.
Keywords: Jazz chords; pop music; guitar playing